2019
DOI: 10.1590/2179-8087.008415
|View full text |Cite
|
Sign up to set email alerts
|

Technologies for Jatoba Seedling Formation

Abstract: This research evaluated protected environment and substrates for jatoba seedling. Two protected environments were used: (i) black shading screen on the sides and roof; and, (ii) black shading screen on the sides and thermal-reflective aluminized screen on the roof. In each environment the following substrates formulated with cattle manure (M) and vermiculite (V) were tested: 100% M; 90% M + 10% V; 80% M + 20% V; 70% M + 30% V; 60% M +40% V; 50% M + 50% V; 40% M +60% V; 30% M + 70% V; 20% M + 80% V; 10% M + 90%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Other studies have shown that the environment could also affect morphometric evaluation. Hydric stress seems to affect the seedling leaf area [13], and light exposure could also influence some seedling measurements, such as the collar diameter [20]. Hence, it is possible that studies using different conditions could also find variations in the results mentioned here.…”
Section: Seedling Morphological Integrationsmentioning
confidence: 84%
See 3 more Smart Citations
“…Other studies have shown that the environment could also affect morphometric evaluation. Hydric stress seems to affect the seedling leaf area [13], and light exposure could also influence some seedling measurements, such as the collar diameter [20]. Hence, it is possible that studies using different conditions could also find variations in the results mentioned here.…”
Section: Seedling Morphological Integrationsmentioning
confidence: 84%
“…In the literature, it is also possible to find the opposite scenario, in which the given information is consistent with population I but not to population II when the study data is compared to the mean values we found. For instance, the mentioned by Costa et al [20], in which the seedling collar diameter raged from 4.9 to 5.07 mm.…”
Section: Protophilusmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to promote germination, in the commercial seedling production context, there are two main processes, open-field germination, where seeds are directly exposed to environmental conditions such as sunlight and temperature, or germination in a greenhouse, where seeds are exposed to greater temperature and moisture but less sunlight than the production area [21], [22]. These different techniques could also impact seed germination and seedling persistence [23], and aspects that have not yet been explored to E. edulis.…”
Section: Introductionmentioning
confidence: 99%